35. IMPROVING QUALITY OF LIFE AND PSYCHOSOCIAL HEALTH FOR PENILE CANCER AFTER ENDOSCOPIC LYMPHADENECTOMY (Vietnam Journal of Community Medicine, 2024)
Background: Penile cancer is a rare but aggressive squamous cell carcinoma affecting the male genitalia. Penile cancer’s psychological impact extends beyond diagnosis, encompassing the consequences of treatment and unique cancer-related distress. Aims: To Improve Quality of Life and Psychosocial Health for Penile Cancer after endoscopic lymphadenectomy at Binh Dan hospital. Materials and Methods: It is a cohort study with 14 patients, at 2022. Data analyzed included quality of life, psychosocial effects, urinary symptoms, and sexual function. Results: minimally invasive endoscopic lymphadenectomy improved QoL, but did not improving sexual function and urinary problems. Conclusions:Minimally invasive treatment methods, including endoscopic inguinal lymphadenectomy for penile cancer, help preserve higher QoL.. Personal support, including educational solutions, group support and family counseling, is essential to recovery from treatment.
Keywords: Penile cancer, video endoscopic inguinal lymphadenectomy, Quality of life.